2011
DOI: 10.1016/j.soncn.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Measurement of Adherence to Oral Antineoplastic Agents

Abstract: OBJECTIVES:The increase in oral anticancer medications with complex regimens creates a need to assure patients are taking therapeutic dosages as prescribed. This article reviews the assessment and measurement of adherence to oral antineoplastic agents. DATA SOURCE:Research and journal articles from CINAHL and Pub Med. CONCLUSION:Assessing and measuring adherence to oral antineoplastic should include three dimensions: the percentage of medications taken, the duration, and the timing of taking the medication. IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 83 publications
(108 reference statements)
0
21
0
2
Order By: Relevance
“…This result was contrary with two previous local studies done among hypertensive and diabetic patients (Hassan et al, 2006;Ramli et al, 2012) although only latter study showed significant association. However, unlike other drugs for chronic diseases, capecitabine is often recognized as the oral drug with complex regimen due to the complexity in administration of the drug (Spoelstra and Given, 2011) thus sufficient information on treatment is strictly required. Even though each of the patients was provided with individual capecitabine treatment handbook in their preferred language, communication barrier cannot be ruled out.…”
Section: Adherence To Capecitabine Treatment and Contributing Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was contrary with two previous local studies done among hypertensive and diabetic patients (Hassan et al, 2006;Ramli et al, 2012) although only latter study showed significant association. However, unlike other drugs for chronic diseases, capecitabine is often recognized as the oral drug with complex regimen due to the complexity in administration of the drug (Spoelstra and Given, 2011) thus sufficient information on treatment is strictly required. Even though each of the patients was provided with individual capecitabine treatment handbook in their preferred language, communication barrier cannot be ruled out.…”
Section: Adherence To Capecitabine Treatment and Contributing Factorsmentioning
confidence: 99%
“…Challenges in adhering to oral chemotherapy may be different from other medications for chronic diseases due to the complexity of certain oral chemotherapy regimens. Some oral chemotherapy such as capecitabine and lapatinib often associated with complex cyclic schedules, drug-free period and more adverse events (Spoelstra and Given, 2011). Due to these challenges, patients with poor adherence may not receive the full benefit of treatment and may consequently experience suboptimal outcomes, poor survival rates, potential adverse events and increase cost burden related to hospitalization (Ruddy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, permite também que o paciente tenha melhor qualidade de vida, pois possibilita a continuidade de suas atividades diárias e a convivência familiar, além de dispensar a necessidade de internação para realizar o tratamento (2) . Outras vantagens estão relacionadas ao fato de ser indolor e não requerer profissional especializado na administração, além de ocasionar efeitos colaterais significativamente menores quando comparados com os quimioterápicos administrados por outras vias (3) .…”
Section: Introductionunclassified
“…Well-conducted randomized controlled trials (RCTs) are needed in further research to better understand adherence impact and other essential outcomes in hematological cancers. In addition, future studies implementing adherence interventions should 1) define adherence and how it will be measured in advance of study design and launch 39 and 2) measure relevant practical outcomes such as humanistic or economic outcomes, to examine intervention effectiveness on the adherence behavior outcome as well as factors relevant to the patient and/or the health care delivery system. Moreover, the follow-up time periods reported in the retained studies of this review were relatively short-term periods (e.g., 6 months or less).…”
Section: Implications For Researchmentioning
confidence: 99%